أحكام الهجرة في الشريعة الإسلامية (مجلة ابحاث كلية التربية الاساسية, 2008)
هذا البحث يتكلم عن حكم الهجرة في الشريعة الاسلامية وقد بحثت ذلك مبتدئاً بالتعريف بالهجرة في اللغة و الشرع , وأحكامها في القران والسنة والفقه الإسلامي وبينت أن الشريعة جعلت الهجرة من المواضيع التي تراد لغيرها فهي لا تراد لذاتها والذي يفرضها هو المصلحة المتعلقة بالدين والنفس والمال فإذا كانت المصلحة لا تتحقق إلا بالهجرة فان الهجرة تجب على المسلم وإذا لم تحقق الهجرة ذلك لم تجب الهجرة اصلاً وعلى ذلك قد تجب الهجرة على شخص دون شخص وفي زمان دون زمان وفي مكان دون مكان سواء كانت في بلد مسلم او غير مسلم على ان لا يكون مع الجيش المحارب للمسلمين ثم أنهيت البحث بخاتمة بينت فيها نتائج وتوصيات توصي بالبحث في ضوء المقاصد الكبرى في المسائل المرتبطة بالمتغيرات والمبنية على المصالح.This study talks about the legal judgment of AL-Hijrah (migration) in the Islamic legislation (AL-Sharia'a).This subject is approached in language, the Glorious Quran, AL-Sunnah(the prophet tradition), and Islamic figh,. In this study, it has been explained that used not as an end in itself, but in relation to other issues. What decides its necessity is the benefit related to religion, the soul and money .So, if the benefit cannot be achieved except by AL-Hijrah (migration), then it will be the Muslim's obligation (duty), and if it did not achive that ,it would not be an obligation . Building on that , AL-Hijrah might be an obligation (duty) for one person rather than another, in a certain time rather than another, and in a certain place rather than another, whether the person is in a Muslim country or in a non –Muslim country provided that he is not with an army which fights the Muslims and occupies their territory. The study is concluded with some findings and recommendations calling for making more investigations in the light of the main purposes.